The Analysis of Time Series: An Introduction - Christopher Chatfield (USA Chapman & Hall, 2004)
"Since 1975, The Analysis of Time Series: An Introduction has introduced legions of statistics students and researchers to the theory and practice of time series analysis. The sixth edition provides an accessible, comprehensive introduction to the theory and practice of time series analysis. The treatment covers a wide range of topics, including ARIMA probability models, forecasting methods, spectral analysis, linear systems, state-space models, and the Kalman filter. It also addresses nonlinear, multivariate, and long-memory models. The author has carefully updated each chapter, added new discussions, incorporated new datasets, and made those datasets available at www.crcpress.com."--BOOK JACKET
Keywords: Social Sciences (3GdYdhe GdGLJeGYjIs; Time-series analysis; General